(untitled) (Jurnal Manajemen dan Kewirausahaan, 2009)
Furniture products from Pasuruan, are not known in neighboring sub-district and regency areas, but also in East Java. Although many mid-scale and large organizations went bankrupt because of the tough economic crisis, this small-scale businesses remain operating without any serious hindrance. The main aims of this research generally are to analyze of using the furniture production factors, to analyze the combination of furniture products that can be produced by the craftsman. This research was done in Pasuruan. The respondents were consisting of 49 furniture craftsman. The result of this research showed that the usage of furniture production factors had not been optimal yet. The combination of furniture products that can be developed optimally by the craftsman generally are 15 table, chair; 14, 1 door wardrobe, and 15, 1 meter of buffet; 16 dressing table; 12, 2 doors wardrobe; 11, 2 meters of buffet; 9, 3 doors wardrobe and 10 bed.